Magnetic filter - Gorobets, Svetlana; Gorobets, Oksana; Bondar, Natalia (My University, 2001)
The proposed magnetic filter that may have a broad application in chemistry, metallurgy, mechanics, power engineering and biological industry can be used for purification of fluid mediums, and natural and sewage water from ferromagnetic and nonferromagnetic impurities.
Keywords: високо градієнтні магнітні поля; высоко градиентные магнитные поля; high gradient magnetic fields; дисперсні частинки; дисперсные частицы; dispersed particles; фільтр; фильтр; filter; кафедра готельно-ресторанної справи